Evaluasi Pelaksanaan Pembelajaran Daring pada Virtual Learning Environment UK Petra Melalui Integrasi Metode Kansei Engineering dan QFD - Natalia Ratna Dewi Lesmono; Herry Christian Palit (Jurnal Titra, 2023)
The implementation of online learning at UK Petra since 1st Semester 2019/2020 has drawn criticism and suggestions from lecturers and students which are channeled through ELTC. Complaints about the implementation of online learning occur in e-learning material/content, e-learning interactive media, and Virtual Learning Environment (VLE). The complaint relates to the e-learning tools used. This research was carried out to select each e-learning tool that was by Kansei words. In 2nd Semester 2020/2021 academic year, the assessment of the learning aspect with the lowest score of 1.95-2.00 was VLE UK Petra (Lentera). Various complaints about the use of the Lentera, such as information that is too crowded, the location of the features is not clear then causing the failure, and the presentation of information that is not clear. Evaluation of the implementation of online learning at Lentera and Google Classroom also needs to be done. The evaluation process is carried out by integrating the Kansei Engineering and Quality Function Deployment methods. Using the average assessment results with semantic differential scale, Google Classroom is a good e-learning tool for every Kansei words. There are 11 proposed improvements that can be applied in Lentera